Students' Perceptions And Preferences Regarding Moral Reasoning Through Online Counseling: A Systematic Study - Achmad Dzikri Fanshabi; Dede Rahmat Hidayat (Al-Makki Publisher, 2023)
The level of moral reasoning is very important for children to influence ethics. A student's moral reasoning can increase the desire to apply good morals to students. This study discusses online counseling to improve moral reasoning. The purpose of this study was to explain students' perceptions and preferences for online counseling services to help improve moral reasoning. The systematic review was carried out by the Systematic Review and Meta-Analysis (PRISMA) approach. Initially, there were 80 articles from three databases as follows: PubMed (6 articles), CINAHL (71 articles), and SINTA (3 articles). After reading the title and abstract, 72 articles were eliminated because the title was not under the purpose of the study, and one abstract was irrelevant in content. So, six articles (five articles in the Indonesian context and one article in the Malaysian context) were analyzed.